Morbidity and Mortality Profile of Neonates Admitted in Neonatal Intensive Care Unit - Paudel, Pradip Kumar; Bhandari, Prakreeti; KC, Nawaraj; Devkota, Bibek (Journal of Nepal Health Research Council, 2024)
Background: The neonatal period faces the greatest risk of death as they are vulnerable to sepsis, birth asphyxia, hypoxic injuries etc. A substantial disparity exists in NMR between Nepal and other developed countries and among different provinces of Nepal as well. This study was conducted to describe the pattern of neonatal admission, and immediate hospital outcomes from NICU located in a remote part of Nepal.Methods: This prospective study was conducted in The Province Hospital, Karnali, Nepal over a period of six months (June 2021 to Dec 2021 AD). The variables used were neonatal age, sex, gestation, birth weight, maternal age, mode and place of delivery. Neonatal morbidities and final outcomes at discharge were recorded in a predesigned proforma.Results: A total of 396 neonates included, the majority were inborn 283(71%), male 241(61%), term 301(76%) and had normal birth weight 279 (70.4%). Neonatal sepsis 188(37.2%), prematurity 95(24%), and birth asphyxia 55(15.2%) were main indications for hospitalization. The majority 337(85%) improved after treatment, while 33(8.3%) died, 12 (3%) left against medical advice and 14(3.5%) cases were referred. Preterm neonates had thrice the risk of mortality than term neonates (OR =3.27). Low birth weight (< 2500 grams) had higher odds of poor outcomes (OR =3.5). Low maternal age (<20 years), prematurity, LBW, mechanical ventilation and inotrope use were predictors of poor outcomes. Conclusions: Neonatal sepsis, prematurity and perinatal asphyxia were the most common causes of NICU admissions. Mechanical ventilation, inotropes use, extreme prematurity, low birth weight and younger age of the mother were predictors of poor outcome. Keywords: Karnali; morbidity; mortality; neonates.